PENGARUH KUALITAS PELAYANAN, BRAND EQUITY, DAM KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN STUDI KASUS PADA OUTLET DEAR SISTERS SIDOARJO - Risdianto Risdianto; Pompong Budi Setiadi; Sri Rahayu (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of service quality, brand equity, and product quality on customer satisfaction. This research was conducted at the Dear Sisters outlet in Sidoarjo, East Java. The research method used in this research is descriptive by using quantitative methods. This study uses primary data, namely the distribution of questionnaires by taking respondents from Dear Sisters outlet customers in the Sidoarjo branch, East Java. This study used random sampling with a total of 50 respondents from the Dear Sisters outlet. The analytical method used is multiple regression analysis which is processed using the SPSS application. The results of this study indicate that the service quality variable has no effect on customer satisfaction, the brand equity variable has a positive effect on customer satisfaction and the product quality variable has no effect on customer satisfaction. And the variables of service quality, brand equity and product quality simultaneously affect customer satisfaction